2017
DOI: 10.1155/2017/3121989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tetramethylpyrazine on Atherosclerosis and SCAP/SREBP‐1c Signaling Pathway in ApoE−/− Mice Fed with a High‐Fat Diet

Abstract: Lipid metabolism dysregulation plays a crucial role in the occurrence of atherosclerosis (As). SCAP/SREBP signaling is the main pathway for regulating lipid metabolism. Tetramethylpyrazine (TMP), a Traditional Chinese Medicine (TCM) for treating angina pectoris, has antiatherosclerotic effects and ameliorates blood lipids disturbance. However, its precise mechanism remains unclear. This study investigated the mechanism of TMP in ameliorating As in mice model. After six weeks of high-fat diet, 30 ApoE−/− mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…TMP has analgesic [ 58 ], anti-aging [ 59 ], antidiabetic [ 60 ], anti-inflammatory [ 61 ], anti-obesity [ 62 ], anti-oxidation [ 63 ], cholesterol-lowering [ 64 ], and neuroprotective [ 65 ] activities. Many studies continue to explore the physiochemical properties and biological activities of TMP and its structural derivatives, hoping to determine the medical potential of such compounds.…”
Section: Discussionmentioning
confidence: 99%
“…TMP has analgesic [ 58 ], anti-aging [ 59 ], antidiabetic [ 60 ], anti-inflammatory [ 61 ], anti-obesity [ 62 ], anti-oxidation [ 63 ], cholesterol-lowering [ 64 ], and neuroprotective [ 65 ] activities. Many studies continue to explore the physiochemical properties and biological activities of TMP and its structural derivatives, hoping to determine the medical potential of such compounds.…”
Section: Discussionmentioning
confidence: 99%
“…65 Another study showed that the traditional Chinese medicine Tetramethylpyrazine, used for angina pectoris treatment, inhibits atherosclerosis progression and improves fat metabolism disorders via PAQR3 downregulation and SCAP/SREBP-1c signaling suppression in high-fat diet administered ApoE −/− mice, likely involving PI3K/Akt/mTORC1 signaling. 66…”
Section: Dovepressmentioning
confidence: 99%
“…Chuanxiong [15]. According to a recent review, TMPZ could attenuate atherosclerosis by suppressing lipid accumulation in macrophages [16], alleviation of lipid metabolism disorder [17], and attenuation of oxidative stress [18]. However, since atherosclerosis is a chronic illness involving multiple cells and cytokines [19], besides lipoprotein metabolism and oxidative stress, other possible targets of TMPZ on atherosclerosis remain unexplored.…”
Section: Tetramethylpyrazine (Tmpz) Is a Member Of Pyrazines Derived mentioning
confidence: 99%